Incentive distortions in decentralized systems of governance – why is financing decentralized systems so difficult? - Torben Dall Schmidt (European Regional Science Association (ERSA), 2004)
National governments often choose to delegate tasks and burdens to lower levels in a comprehensive system of administration. Local and regional governance thereby becomes an important factor in policy implementation. This paper focuses on the incentive problem that follows from such a delegation of competences to collect taxes and do lending at the local level in a multi-level geo-administrative system. The paper uses the Danish administrative system to illustrate the actual outcomes from such incentive problems. A two-step estimation procedure will be used to derive results on the importance of incentive problems in multi-level geo-administrative systems. Setting up elaborate administrative systems will introduce agency problems that lead to inefficiencies in both local and national governance.
Keywords: 330